2017
DOI: 10.15282/jmes.11.4.2017.14.0280
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modelling prediction by using wake oscillator model for vortex-induced vibrations

Abstract: Explorations by oil and gas companies have moved from shallow to deep water to satisfy consumers' changing needs. A circular-shaped cylinder structure placed in deep water is also known spar platform, is normally floated and subjected to severe conditions which cause unpleasant motions and fatigue damage to the structure. Wake oscillator model is considered a semi-empirical model that is most suitable for the evaluation of Vortexinduced Vibrations (VIV) structure features during the design stage. This work foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The validation were made succeeded previous coupling model by Hussin et al (2017) and comparison between analytical model by Facchinetti et al (2004) and experimental data from Govardhan and Williamson (2000) are shown in Figure 2. For comparison sake, the low mass ratio m^*=0.52 and low reduced damping ξ=0.0052 are used.…”
Section: Coupling Model Validationmentioning
confidence: 86%
See 1 more Smart Citation
“…The validation were made succeeded previous coupling model by Hussin et al (2017) and comparison between analytical model by Facchinetti et al (2004) and experimental data from Govardhan and Williamson (2000) are shown in Figure 2. For comparison sake, the low mass ratio m^*=0.52 and low reduced damping ξ=0.0052 are used.…”
Section: Coupling Model Validationmentioning
confidence: 86%
“…The angular frequency , derived from Equation 13, produced one or three positive real roots. Based on the solutions, angular frequency using coupling Equations (11) and 12…”
Section: Coupling Systemmentioning
confidence: 99%
“…In order to avoid any sort of equipment failures, it is very important to have a good prevention strategy. Vibration is a powerful tool that helps to provide a good information regarding the state of the assets either equipment or structure [4][5][6][7]. For machinery monitoring, vibration-based is one of the most popular techniques used in order to maintain and sustain industrial assets due to its simple, low-cost and easiness of implementation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Formerly, in fault diagnosis, CNN is only applied to automatically select features from the generated vibration signal which is in onedimensional input of time domain. Vibration signals provide a useful information regarding the state of the assets either equipment or structure [7][8][9]. Although the direct usage of CNN on the generated vibration signals is widely used and step-less, only time data could be extracted whereas the significant spatial data of the signals which in this case is the sequence of frequency as stated by Janssens et al [10] could not be interpreted.…”
Section: Introductionmentioning
confidence: 99%